2019
DOI: 10.1111/jicd.12424
|View full text |Cite
|
Sign up to set email alerts
|

Association of A‐197G polymorphism in interleukin‐17 gene with chronic periodontitis: Evidence from six case‐control studies with a computational biology approach

Abstract: Aim The aim of the present study was to evaluate the association of interleukin‐17 (IL‐17) A‐197G gene polymorphism with chronic periodontitis (CP) in a case‐control study, a meta‐analysis, and an in silico approach. Methods In the case‐control study, 122 cases with CP and 126 healthy controls were recruited; IL‐17 A‐197G genotyping was performed by polymerase chain reaction‐restriction fragment length polymorphism. In the meta‐analysis, comprehensive literature retrieval was performed on valid databases to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Moreover, the percentage of mucosal-associated invariant T cells (MAIT) producing IL-17 is higher in PD patients than in controls [51]; thus, the dysregulation of IL-17 could play a role in PD development. Importantly, polymorphisms in the IL-17 gene have been found to impact susceptibility to the disease; for instance, a metaanalysis by Farmohammadi showed that the AA genotype of the A-197G polymorphism has been associated with an increased odds ratio (OR) [52]. Interestingly, particular genetic profiles may influence the presence of pathogenic bacteria.…”
Section: Interleukinsmentioning
confidence: 99%
“…Moreover, the percentage of mucosal-associated invariant T cells (MAIT) producing IL-17 is higher in PD patients than in controls [51]; thus, the dysregulation of IL-17 could play a role in PD development. Importantly, polymorphisms in the IL-17 gene have been found to impact susceptibility to the disease; for instance, a metaanalysis by Farmohammadi showed that the AA genotype of the A-197G polymorphism has been associated with an increased odds ratio (OR) [52]. Interestingly, particular genetic profiles may influence the presence of pathogenic bacteria.…”
Section: Interleukinsmentioning
confidence: 99%